Influence of Promoter Type on Bimetallic Co-Ni/Al 2O3 Catalyst for Steam Reforming of Glycerol - Cheng, C. K.; Jolius, Gimbun; Chin, S. Y. (UMP, 2012)
Biodiesel is produced from a variety of renewable sources including waste cooking oil. However, its production has led to a glut of glycerol (a by-product, in the amount of 1 mol of glycerol for every three of fatty acid methyl esters). Glycerol presently has low-level and limited use in pharmaceuticals production. The present work deals with steam reforming of glycerol over a bimetallic Co-Ni/Al2O3 catalyst system promoted by 2.5wt% alkaline earth oxides (AEO) and lanthanide oxides (LO). The addition of metal oxide from these two groups reportedly minimizes carbon deposition with possible improvement in product selectivity and syngas production rate. Our objective was to provide a systematic correlation between physicochemical properties of the promoted catalyst and reaction metrics.